The Insanity Defense in Operation - Daniel D. Pugh (Washington University Law Quarterly, 1973)
The purpose of this Article is to describe the problems of the insanity defense and criminal commitment as they appear to a psychiatrist in a hospital for the criminally insane. Viewed from this vantage point, the terrain seems to look quite different from the way it appeared to the Court of Appeals in United States v. Brawner.
Keywords: Psychiatry